Bacteriological investigation of bovine clinical mastitis in two selected farms in Ibadan, Oyo State of Nigeria (2005)
Bacteriological examination was performed on 60 and 40 milk samples of clinical mastitic udders from Akinyele and Iyana Offa farms, Ibadan, respectively. A total of 251 bacterial isolates belonging to 5 bacteriological genera were recovered from the milk of the mastitic cows examined. Approximately 70% and 76% of the Staphylococci isolated from the milk of mastitic cows in Akinyele and Iyana Offa farms, respectively, were coagulase positive. Staphylococcus aureus was the most common pathogen in this study with an incidence of 39.0% while the coagulase-negative Staphylococcus species had an incidence of 3.6%. Other bacteria isolated include Streptococcus agalactiae and Pseudomonas aeruginosa, each with an incidence of 7.6%, while Streptococcus uberis showed an incidence of 18.7% . Escherichia coli and Klebsiella pneumoniae showed an incidence of 11.2% and 12.4%, respectively. The bacteria encountered in this investigation are among the pathogens that have been incriminated as contaminants of fresh milk meant for human consumption and are therefore of public health importance.